2013
DOI: 10.1002/jmv.23556
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the hepatitis B virus presurface and surface gene in patients from eastern China with occult hepatitis B

Abstract: This study was designed to detect and analyze mutations that occur within the presurface and surface (pre-S/S) gene of HBV in patients with occult hepatitis B, and determine their relationship to that disorder. Among 254 HBsAg negative samples of blood collected in eastern China, 183 were positive for anti-HBc alone, 61 were positive for anti-HBe alone, and 10 samples were positive for HBeAg. Within this group, 15 samples were found to be HBV DNA positive by real-time PCR and were designated Group I. A control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
2
19
1
1
Order By: Relevance
“…According to a similar study of HBV genetic diversity in American blood donors, the prevalence of the well-known neutralization escape mutation G145R in the HBV envelope protein was as high as 22% [15]. However, in contrast to those results, in our study, the G145R mutation was heavily underrepresented (2.07%), from which it can be inferred that the genotype B, C and D strains in Northwest China may have less likelihood of vaccine escape [20]. Furthermore, compared to the G145R mutation, several mutations within the major hydrophilic region were detected at high prevalence, such as M134Y and S143T/L.…”
Section: Discussioncontrasting
confidence: 74%
“…According to a similar study of HBV genetic diversity in American blood donors, the prevalence of the well-known neutralization escape mutation G145R in the HBV envelope protein was as high as 22% [15]. However, in contrast to those results, in our study, the G145R mutation was heavily underrepresented (2.07%), from which it can be inferred that the genotype B, C and D strains in Northwest China may have less likelihood of vaccine escape [20]. Furthermore, compared to the G145R mutation, several mutations within the major hydrophilic region were detected at high prevalence, such as M134Y and S143T/L.…”
Section: Discussioncontrasting
confidence: 74%
“…Since the reported mutations were completely different from those reported to be associated with OBI in genotypes B and C [52] , it was suggested by the authors that OBI associated mutations are unique for each HBV genotype. Indeed, several studies comprising genotypes B and C identified G145R/A to be among major mutations responsible for OBI [51][52][53] .…”
Section: Hbs Antigen Mutationsmentioning
confidence: 99%
“…Many recent studies are addressing the possible association of BCP and Pre-C mutations with more severe outcome of liver disease, namely with appearance of ful-the S protein [53,55] .…”
Section: Hbs Antigen Mutationsmentioning
confidence: 99%
“…Some OHB infections in patients with HCC are associated with HBV variants, including preS2‐defective and/or core promoter mutants or X‐mutated strains, which may have pro‐oncogenic activities . HBV preS/S mutations could be one of the reasons why HBsAg is unmeasurable in the HBV‐infected subjects . Chen et al .…”
Section: Possible Mechanisms Involved In Ohb As a Risk Factor In Hccmentioning
confidence: 99%
“…Some OHB infections in patients with HCC are associated with HBV variants, including preS2-defective and/or core promoter mutants or X-mutated strains, which may have pro-oncogenic activities [39]. HBV preS/S mutations could be one of the reasons why HBsAg is unmeasurable in the HBV-infected subjects [79][80][81]. Chen et al [50] suggested that different virological features of HBV are found in HCC patients with OHB when compared with overt HBV in chronic hepatitis B patients with HCC.…”
Section: Possible Mechanisms Involved In Ohb As a Risk Factor In Hccmentioning
confidence: 99%